Creating strategic couplings in global production networks: regional institutions and lead firm investment in the Humber region, UK. (4th March 2019) - Dawley, Stuart; MacKinnon, Danny; Pollock, Robert
Abstract: This article aims to unpack and analyse the institutional and political dynamics of strategic coupling from a host region perspective, adopting an actor-centred approach that focuses on regional institutions' efforts to attract and embed lead firm investments within global production networks. We are particularly concerned with understanding the strategic agency and shifting coalitions of actors that create couplings and shape their evolution over time. This involves opening up the institutional underpinnings of strategic couplings by focusing more specifically on the key episodes in their creation and the organisation of the temporary coalitions that do the work of creating couplings. This approach is operationalised through a case study of the Siemens offshore wind turbine plant in the Humber region of England. In conclusion, we emphasise the need for regional institutions to develop adaptive coupling creation strategies that co-evolve with the reconfiguration of production networks and the reshaping of national institutional and political environments.